Metastatic Hepatocellular Carcinoma Masquerading as Acute Diverticulitis. Issue 11 (24th November 2022) - Brotherton, Tim; Al-Taee, Ahmad M.; Carpenter, Danielle; Cheesman, Antonio R.
ABSTRACT: Colorectal cancer may masquerade as acute diverticulitis. Our case is a 71-year-old man who presented to the emergency department with abdominal pain and was diagnosed with acute diverticulitis. He was ultimately found to have metastatic hepatocellular carcinoma to the colon without any evidence of diverticular disease on colonoscopy. Although the most common malignancy to masquerade as diverticulitis is colorectal cancer, metastatic deposits should also be considered, especially in patients with a history of extracolonic malignancy.